2017
DOI: 10.18632/oncotarget.18647
|View full text |Cite
|
Sign up to set email alerts
|

MiR-367 regulates cell proliferation and metastasis by targeting metastasis-associated protein 3 (MTA3) in clear-cell renal cell carcinoma

Abstract: Clear-cell renal cell carcinoma (ccRCC) is an aggressive and malignant kidney cancer which has the worst prognosis. Although microRNAs (miRNAs) have recently been identified as a novel class of regulators in oncogenesis and metastasis, there are few studies on their participation in ccRCC. In the present study, we observed that miR-367 expression was increased in both human ccRCC tissues and cell lines. Cell proliferation was evaluated by MTT assay and 5-Ethynyl-2′-deoxyuridine (EdU) assay kit, which indicated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 36 publications
1
22
0
Order By: Relevance
“…MTA3 presented the highest fold change in normal and glioma tissues (Figure B). MTA3 has been reported to be a tumor inhibitor in several tumors, including glioma . Thus, we chose MTA3 for subsequent experiments.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…MTA3 presented the highest fold change in normal and glioma tissues (Figure B). MTA3 has been reported to be a tumor inhibitor in several tumors, including glioma . Thus, we chose MTA3 for subsequent experiments.…”
Section: Resultsmentioning
confidence: 99%
“…MTA3 has been reported to be a tumor inhibitor in several tumors, including glioma. [21][22][23][24] Thus, we chose MTA3 for subsequent experiments.…”
Section: Mta3 Is a Target Of Mir-4425 In Gliomamentioning
confidence: 99%
“…Our study confirmed the role for miR‐367‐3p as a tumour suppressive miRNA in cervical cancer. However, there are also studies reporting an oncogenic function of miR‐367‐3p with respect to tumour progression . These findings report a disparate function for miR‐367‐3p in tumour progression and indicate that the precise expression status and function of miR‐367‐3p may be dependent on the type of tumour involved.…”
Section: Discussionmentioning
confidence: 99%
“…A number of recent studies have identified a variety of deregulated miRNAs in ccRCC, including miR-224 (27), miR-502 (28), miR-543 (18) and miR-645 (29). miRNAs are involved in several biological and pathological processes, including ccRCC occurrence and development (30)(31)(32). Previous studies have also identified several deregulated miRNAs in ccRCC, whereby oncogenic miRNAs are upregulated and tumor suppressor miRNAs are downregulated (17,33).…”
Section: Discussionmentioning
confidence: 99%